(untitled) (Acta Scientiarum. Language and Culture, 2013)
Resenha GAUTHIER, Guy. O documentário: um outro cinema. Tradução Eloisa Araújo Ribeiro. Campinas: Papirus, 2011. 432 p. ISBN 978-85-308-0939-3